The leading causes of death in the US and Mexico’s pediatric population are related to violence: a note on secondary analyses of registered deaths from 2000 to 2022 - Castilla-Peon, Maria F.; Rendón, Pablo L.; Gonzalez-Garcia, Nadia (Frontiers in Public Health, 2024)
Introduction: our objective was to analyze the trends in the leading causes of death among the pediatric population aged 1-19 years in Mexico and the United States (US) from 2000 to 2022. Methods. Data for Mexico were sourced from the National Institute of Statistics and Geography (INEGI), while the US data were extracted from the Centers for Disease Control and Prevention's Wide-ranging Online Data for Epidemiologic Research (CDC-WONDER) databases. Results. Homicide has been the leading cause of death since 2017 in Mexico and since 2019 in US youths aged 1-19. In Mexico, it reached 6.5 deaths per 100,000 people in 2022. Despite the overall pediatric mortality decline from 2000 to 2022 in both countries, the pediatric homicide rate has increased by 93.3% and 35.8% In Mexico and the US, respectively, and suicide by 86.6% and 36.9%. In both countries, death by firearm-related injuries had risen in a parallel sense. In the US, deaths by drug overdose and poisoning have increased by 314.8%. Conclusions. Despite advancements in infant healthcare over the past two decades in Mexico, there remains a significant gap in the provision of healthcare services to the adolescent population. Addressing issues related to violence, mental health, and substance abuse through targeted public policies is imperative for both Mexico and the US, especially given their shared border region.